2021
DOI: 10.12965/jer.2142488.244
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between heart rate at first ventilatory threshold on treadmill and at 6-min walk test in coronary artery disease patients on β-blockers treatment

Abstract: The purpose of this study was to verify the accuracy of the agreement between heart rate at the first ventilatory threshold (HRVT1) and heart rate at the end of the 6-min walk test (HR6MWT) in coronary artery disease (CAD) patients on β-blockers treatment. This was a cross-sectional study with stable CAD patients, which performed a cardiopulmonary exercise test (CPET) on a treadmill and a 6-min walk test (6MWT) on nonconsecutive days. The accuracy of agreement between HRVT1 and HR6MWT was evaluated by Bland–Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
1
0
2
Order By: Relevance
“…Os autores encontraram concordância entre a FC avaliada ao final do TC6min e o LV1, sugerindo que a FC ao final do TC6min foi adequada para prescrever e monitorar o EA nessa população. 25 …”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os autores encontraram concordância entre a FC avaliada ao final do TC6min e o LV1, sugerindo que a FC ao final do TC6min foi adequada para prescrever e monitorar o EA nessa população. 25 …”
Section: Discussionunclassified
“…The authors found an agreement between HR assessed at the end of the 6MWT and VT1, suggesting that HR at the end of the 6MWT was adequate to prescribe and monitor AE in this population. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation